Efficacy of atrazine 500 g/l Herbicide against Various Types of Weeds and Its Impact on Maize Plants (Zea mays Linnaeus) - Ibrohim Ibrohim; Hidayat Pujisiswanto; Niar Nurmauli; Herry Susanto (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2023)
Atrazine 500 g/l is a selective herbicide that can be applied during pre- or post-growth of corn. This study aimed to determine the effective level of dosage in controlling weeds in the corn planting area and its impact on growth and corn yields. The study was conducted at the Experimental Garden of Universitas Lampung, South Lampung, and the Weed Laboratory of the Faculty of Agriculture, Universitas Lampung, from August to November 2022. The study used a Randomized Block Design (RBD) with seven treatments and four replications. The treatment consisted of 5 herbicide doses (Atrazine 500 g/l (500, 750, 1,000, 1,250, and 1,500 g/ha), manual weeding, and control. The results showed that Atrazine 500 g/l at doses of 750 - 1,500 g/ha effectively controlled the growth of total weeds, broadleaf and grass weeds, Digitaria ciliaris, and Richardia brasiliensis. While at doses of 500–1,500 g/ha, it effectively controlled Eleusine indica, Cleome rutidosperma, and Commelina benghalensis. Those doses did not poison, and did not inhibit growth, and the yield of maize.